Chick lit and postfeminism - Harzewski, Stephanie, 1974- (Cultural frames, framing culture., 2011)
The author offers a scholarly dissection of "chick lit" from a post-feminist perspective. She analyzes the novel Bridget Jones' Diary and the HBO series Sex and the City while making parallels back to writings of Jane Austen and the Victorian novel in general. She looks at what these works say about women in society and whether they are just an escape or a serious reflection of women's concerns